Unsettled years. Currency on the borders of the Kingdom of Poland and the Teutonic Order during the years 1410-1466 - Musiałowski, Adam (Acta Archaeologica Lodziensia, 2018)
An analysis of 46 coin hoards discovered in the border area of the Kingdom of Poland and the Teutonic Order inclines one to the belief that the series of military conflicts between these two states had no significant impact on their economic relations or on monetary circulation. The structure of the hoards reflects the material possessions of the local population, as well as their needs as consumers on both sides of the frontier.